Effect of losartan on performance and physiological responses to exercise at high altitude (5035 m). Issue 1 (7th January 2021) - Lucas, Samuel J E; Malein, William L; Thomas, Owen D; Ashdown, Kimberly M; Rue, Carla A; Joyce, Kelsey E; Newman, Charles; Cadigan, Patrick; Johnson, Brian; Myers, Stephen D; Myers, Fiona A; Wright, Alexander D; et al.
Abstract : Objective: Altitude-related and exercise-related elevations in blood pressure (BP) increase the likelihood of developing pulmonary hypertension and high-altitude illness during high-altitude sojourn. This study examined the antihypertensive effect and potential exercise benefit of the angiotensin II receptor antagonist losartan when taken at altitude. Methods: Twenty participants, paired for age and ACE genotype status, completed a double-blinded, randomised study, where participants took either losartan (100 mg/day) or placebo for 21 days prior to arrival at 5035 m (Whymper Hut, Mt Chimborazo, Ecuador). Participants completed a maximal exercise test on a supine cycle ergometer at sea level (4 weeks prior) and within 48 hours of arrival to 5035 m (10-day ascent). Power output, beat-to-beat BP, oxygen saturation (SpO2 ) and heart rate (HR) were recorded during exercise, with resting BP collected from daily medicals during ascent. Before and immediately following exercise at 5035 m, extravascular lung water prevalence was assessed with ultrasound (quantified via B-line count). Results: At altitude, peak power was reduced relative to sea level (p<0.01) in both groups (losartan vs placebo: down 100±29 vs 91±28 W, p=0.55), while SpO2 (70±6 vs 70±5%, p=0.96) and HR (146±21 vs 149±24 bpm, p=0.78) were similar between groups at peak power, as was the increase in systolic BP from rest to peak power (up 80±37 vs 69±33 mm Hg, p=0.56). Exercise increased B-line count (p<0.05), but not differently between groups (up 5±5 vs 8±10, p=0.44). Conclusion: Losartan had no observable effect on resting or exercising BP, exercise-induced symptomology of pulmonary hypertension or performance at 5035 m.